2022
DOI: 10.1080/2162402x.2022.2075204
|View full text |Cite
|
Sign up to set email alerts
|

TH-MYCN tumors, but not tumor-derived cell lines, are adrenergic lineage, GD2+, and responsive to anti-GD2 antibody therapy

Abstract: Neuroblastoma is a commonly lethal solid tumor of childhood and intensive chemoradiotherapy treatment cures ~50% of children with high-risk disease. The addition of immunotherapy using dinutuximab, a monoclonal antibody directed against the GD2 disialoganglioside expressed on neuroblasts, improves survival when incorporated into front-line therapy and shows robust activity in regressing relapsed disease when combined with chemotherapy. Still, many children succumb to neuroblastoma progression despite receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…While many reasons could account for the response failure of anti-GD2 immunotherapy for a fraction of patients, one of the hypotheses is that lineage switching may lead to low abundance of GD2 expression due to downregulation of GD2 synthase genes. A recent study has shown that cell lines derived from TH-MYCN transgenic tumors lost GD2 expression, accompanied with switching of cell state from ADRN to MES 76 . Another study further supported that neuroblastoma state transition to MES confers resistance to anti-GD2 antibody via reduced expression of ST8SIA1 77 .…”
Section: Resultsmentioning
confidence: 99%
“…While many reasons could account for the response failure of anti-GD2 immunotherapy for a fraction of patients, one of the hypotheses is that lineage switching may lead to low abundance of GD2 expression due to downregulation of GD2 synthase genes. A recent study has shown that cell lines derived from TH-MYCN transgenic tumors lost GD2 expression, accompanied with switching of cell state from ADRN to MES 76 . Another study further supported that neuroblastoma state transition to MES confers resistance to anti-GD2 antibody via reduced expression of ST8SIA1 77 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in developing GD2-based CAR T and CAR NKT therapies have provided additional evidence showing the potential of anti-GD2 immunotherapy for patients with relapsed disease 41,44 . The Th-MYCN mouse model in the 129X1/SvJ background was responsive to anti-GD2 immunotherapy 81 . Here we focused on the Dbh-iCre;CAG-MYC syngeneic models and tested their responses to immunotherapies and targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…If higher VN integrated density is confirmed in VN/PEG hydrogels, the experiments should assess whether it is due to the presence of both synthesized and PEGylated VN (cells may preferentially grow on PEGylated VN spots or pericellularly reorganize PEGylated VN), or because an increased cell VN synthesis driven by PEGylated VN. Despite no statistical differences, the fact that VN expression is retained in vitro conditions indicates that VN/PEG hydrogels are susceptible for translational combinatory therapy studies as occurs with GD2 ( KO et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%